LivSim: An Open-Source Simulation Software Platform for Community Research and Development for Liver Allocation Policies. Issue 2 (February 2018) - Kilambi, Vikram; Bui, Kevin; Mehrotra, Sanjay
Abstract : Supplemental digital content is available in the text.